2001
DOI: 10.1071/am01101
|View full text |Cite
|
Sign up to set email alerts
|

Long-term changes in the mammal fauna of logged, coastal forests near Bega, New South Wales, detected by analysis of dog and fox scats.

Abstract: In 1996, a study was undertaken to identify the mammals in Mumbulla State Forest near Bega on the south coast of New South Wales through the collection of dog and fox scats in the area. A total of 1121 scats was collected. The objective was to assess the changes in mammal fauna since 1981 when the first detailed analysis of predator scats was made after the forest was first logged for woodchips and sawlogs under the Eden woodchip agreement. The most notable change between the two surveys was a decrease in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…Due to the unknown time delay between prey ingestion and defaecation, the location in which the prey animals live cannot be accurately determined, so this technique is useful only for detecting the species presence within a general area. However, Lunney et al (2002) showed that on average Feral Dogs and Foxes defaecate within a 2 km radius of the site of prey ingestion.…”
Section: Predator Scat Collectionmentioning
confidence: 98%
“…Due to the unknown time delay between prey ingestion and defaecation, the location in which the prey animals live cannot be accurately determined, so this technique is useful only for detecting the species presence within a general area. However, Lunney et al (2002) showed that on average Feral Dogs and Foxes defaecate within a 2 km radius of the site of prey ingestion.…”
Section: Predator Scat Collectionmentioning
confidence: 98%
“…An earlier study of fox movement patterns had revealed that the mean width of a red fox home range in the regions of Dalby, Meandarra and Moonie in the BBS to be approximately 3 km (C. Graham unpublished data, Lunney et al 2002).The mean width of home ranges was used as a buffer distance to delineate the landscape where the fox likely obtained its food directly related to each scat sample (Lunney et al 2002). The landscape characteristics were measured within this buffer distance surrounding each diet sample (Table 1).…”
Section: Landscape Covariatesmentioning
confidence: 99%
“…Lunney et al . (1990, 2002) observed the diets of what where assumed to be Dingo and Dingo–Dog hybrids and Red Fox ( Vulpes vulpes ) in logged coastal forests near Bega on the far south coast of New South Wales, at two time periods separated by nearly 15 years. Although Dingo and/or Dingo–Dog hybrids preyed upon threatened species such as the Long‐nosed Potoroo ( Potorous tridactylus ) in both early and later successional forest stands, the level of predation was insufficient to cause the local demize of that species.…”
Section: The Value Of Debatementioning
confidence: 99%
“…Lunney et al . (1990Lunney et al . ( , 2002 observed the diets of what where assumed to be Dingo and Dingo-Dog hybrids and Red Fox ( Vulpes vulpes ) in logged coastal forests near Bega on the far south coast of New South Wales, at two time periods separated by nearly 15 years.…”
Section: The Value Of Debatementioning
confidence: 99%